Vocal Loudness Variation With Spectral Slope - Titze, Ingo R. (J Speech Lang Hear Res, 2020)
OBJECTIVE: This investigation addresses the loudness variations in sones achievable with spectral slope variations (higher harmonic energy) in human vocalization and compares it to the sound pressure level (SPL) variations typically reported in the voice range profile (VRP). METHOD: The primary methodology was computational. The ISO standard 226 was used to convert SPL values to sones for a 125- to 1000-Hz range of fundamental frequency and a –3 dB/octave to –12 dB/octave range of spectral slope. In addition, a retrospective analysis of human subjects' VRPs was conducted, and the experimental results were compared to the theoretical results. RESULTS: A very small range of SPL variation (less than 5 dB) in the VRP can produce a large range of loudness. The sensitivity can be on the order of 4 sones per dB SPL change. CONCLUSION: For vocalization in the modal register, loudness variation is not well described by SPL change in dB, especially at high fundamental frequencies where the SPL range in the VRP becomes very small but sizeable loudness variations are still possible.